2018
DOI: 10.3390/ma11091546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Laser Melting Process Parameters on Microstructure and Properties of Co-Cr Alloy

Abstract: Due to the rapid melting and solidification mechanisms involved in selective laser melting (SLM), CoCrMo alloys fabricated by SLM differ from the cast form of the same alloy. In this study, the relationship between process parameters and the morphology and macromechanical properties of cobalt-chromium alloy micro-melting pools is discussed. By measuring the width and depth of the molten pool, a theoretical model of the molten pool is established, and the relationship between the laser power, the scanning speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
(45 reference statements)
0
25
0
2
Order By: Relevance
“…CoCrMo powder (60-65% of Co, 26-30% of Cr, 5-7% of Mo) was chosen due to its excellent melting properties, heat resistivity, neutral reaction to the protective environment, and wide range of possible industrial applications [52][53][54]. The granular and morphometric analyses showed that the granules have a mostly spherical shape, which is preferable for better energy absorption [55][56][57]. The initial CoCrMo powder was sifted using an analytical sieving machine AS200 basic (Retsch, Dusseldorf, Germany) with a test sieve (50 µm by ISO 3310-1) and dried using a vacuum oven VO400 (Memmert GmbH + Co. KG, Schwabach, Germany) before processing.…”
Section: Powder Materialsmentioning
confidence: 99%
“…CoCrMo powder (60-65% of Co, 26-30% of Cr, 5-7% of Mo) was chosen due to its excellent melting properties, heat resistivity, neutral reaction to the protective environment, and wide range of possible industrial applications [52][53][54]. The granular and morphometric analyses showed that the granules have a mostly spherical shape, which is preferable for better energy absorption [55][56][57]. The initial CoCrMo powder was sifted using an analytical sieving machine AS200 basic (Retsch, Dusseldorf, Germany) with a test sieve (50 µm by ISO 3310-1) and dried using a vacuum oven VO400 (Memmert GmbH + Co. KG, Schwabach, Germany) before processing.…”
Section: Powder Materialsmentioning
confidence: 99%
“…Cobalt-chromium (Co-Cr) alloys are primarily viable for metal 3D printing in dental prostheses [4]. These alloys demonstrate good tensile strength, elasticity, fatigue resistance, or corrosion resistance [11]. The major constituents of the powder are cobalt and chromium; however, molybdenum, tungsten, silicon, manganese, niobium, cerium, iron, and carbon are also included to improve the properties of the material [9].…”
Section: Introductionmentioning
confidence: 99%
“…The process of making dental restorations by sintering dental alloys basically includes three steps: digital impression, designing virtual restoration, and 3D printing [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Универзитет у Београду, Стоматолошки факултет, Београд, Србија; 2 Универзитет у Марибору, Машински факултет, Београд, Србија;3 Факултет за технологију полимера, Словењ Градец, Словенија;4 Српско лекарско друштво, Академија медицинских наука, Београд, Србија Selective laser melting and sintering technique of the cobalt-chromium dental alloy…”
unclassified